2009
DOI: 10.1097/qad.0b013e328321b778
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 infection of human penile explant tissue and protection by candidate microbicides

Abstract: Objective Factors governing events between exposure of male genital mucosa surfaces and the establishment of infection are poorly understood. Furthermore, little is known about the safety and efficacy of microbicides on male genital mucosa. Design Here we present a novel penile tissue explant model to characterise the mechanisms of HIV-1 infection of male genital tissue and evaluate candidate microbicides. Methods Mucosal explant culture conditions were determined for glans, urethra and foreskin obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0
7

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 46 publications
5
109
0
7
Order By: Relevance
“…Such prototypic non-primary R5 and X4 strains have been widely used to test the susceptibility to HIV infection of a range of tissues including the cervix, prostate gland, foreskin, and penis. 26,[31][32][33][34][35] With use of these two strains, we demonstrated that the human seminal vesicles are selectively infected by macrophage-tropic HIV-1 R5 ex vivo and release infectious virions. The R5 SF162 strain consistently replicated in the seminal vesicle tissues, as assessed by increased reverse transcriptase activity in seminal vesicle supernatants during culture, increased level of viral DNA in the explants, PBMC infection by the viral particles recovered from the infected seminal vesicle supernatants, and in situ detection of infected cells in the explants using immunohistochemistry for HIV p24.…”
Section: Discussionmentioning
confidence: 99%
“…Such prototypic non-primary R5 and X4 strains have been widely used to test the susceptibility to HIV infection of a range of tissues including the cervix, prostate gland, foreskin, and penis. 26,[31][32][33][34][35] With use of these two strains, we demonstrated that the human seminal vesicles are selectively infected by macrophage-tropic HIV-1 R5 ex vivo and release infectious virions. The R5 SF162 strain consistently replicated in the seminal vesicle tissues, as assessed by increased reverse transcriptase activity in seminal vesicle supernatants during culture, increased level of viral DNA in the explants, PBMC infection by the viral particles recovered from the infected seminal vesicle supernatants, and in situ detection of infected cells in the explants using immunohistochemistry for HIV p24.…”
Section: Discussionmentioning
confidence: 99%
“…The skin covering the glans and penis in rhesus monkeys is referred to as the prepuce and is similar to the human foreskin. The histologic architecture and populations of potential HIV/SIV target cells in the foreskins of the two species have been shown to be similar (5,7,25,26,29). For this study, we developed a technique of atraumatically exposing the rhesus monkey prepuce and penile mucosa to SIV.…”
Section: Sequence Alignment Of Retroviral Capsid Regions In Siv Gagmentioning
confidence: 99%
“…In another preclinical test, CVN and two other microbicide candidates currently in clinical trials, i.e., PRO 2000 and PMPA gel (tenofovir), were evaluated in a novel penile tissue explant model (Fischetti et al 2009). It was found that CVN conferred 95% protection against HIV-1 at 11 μg/ml, which is similar to that seen in cervical explants and is a dose 1/500 of that shown to be protective in macaques.…”
Section: Preclinical Test Of Cvn Against Hivmentioning
confidence: 99%
“…In vivo studies with CVN formulated as a gel have shown promising efficacy as a microbicide candidate. In addition, a recent ex vivo test showed that the antiviral effect of CVN is stronger than that of PRO 2000 (Fischetti et al 2009;Huskens et al 2009), a non-specific polyanion microbicide.…”
Section: Introductionmentioning
confidence: 99%